Safety and immunogenicity of the first Kazakh inactivated vaccine for COVID-19 - Ainur Nurpeisova; Berik Khairullin; Ruslan Abitaev; Kamshat Shorayeva; Kuanish Jekebekov; Elina Kalimolda; Aslan Kerimbayev; Karligash Akylbayeva; Zhandos Abay; Balzhan Myrzakhmetova; Aziz Nakhanov; Zharkinay Absatova; et al. (Taylor & Francis Group, 2022)
This article describes the results of a preclinical safety and immunogenicity study of QazCovid-in®, the first COVID-19 vaccine developed in Kazakhstan, on BALB/c mice, rats, ferrets, Syrian hamsters and rhesus macaques (Macaca mulatta). The study's safety data suggests that this immunobiological preparation can be technically considered a Class 5 nontoxic vaccine. The series of injections that were made did not produce any adverse effect or any change in the general condition of the model animals' health, while macroscopy and histology studies identified no changes in the internal organs of the BALB/c mice and rats. This study has demonstrated that a double immunization enhances the growth of antibody titers as assessed by the microneutralization assay (MNA) and the enzyme-linked immunosorbent assay (ELISA) in a pre-clinical immunogenicity test on animal models. The best GMT results were assessed in MNA and ELISA 7 days after re-vaccination; however, we noted that GMT antibody results in ELISA were lower than in MNA. A comparative GMT assessment after the first immunization and the re-immunization identified significant differences between model animal groups and a growth of GMT antibodies in all of them; also, differences between the gender groups were statistically significant. Moreover, the most marked MNA immune response to the QazCovid-in® vaccine was seen in the Syrian hamsters, while their SARS-CoV-2-specific antibody activity as assessed with ELISA was the lowest.